Adaptation and Implementation of the Global Scales for Early Development (GSED) Tool in Ethiopia - Kalkidan Yibeltal; Atsede Teklehaimanot; Firehiwot Workneh; Nebiyou Fasil; Sarah K. G. Jensen; Theresa I. Chin; Krysten North; Betelhem Haymanot; Alemayehu Worku; Anne CC Lee; Yemane Berhane (Children)
Background: The World Health Organization (WHO) recently developed the Global Scales for Early Development (GSED) tool to address the lack of a population-level metric for early childhood development globally. This paper describes learning from the first experience with the translation, adaptation, and implementation of the GSED tool in Ethiopia. Methods: WHO guidelines were followed to translate and adapt the GSED tool to Amharic. Two Ethiopian child health experts were trained as GSED Master Trainers. The tool was forward translated by two independent translators with previous experience in child development assessment, consensus was obtained, and the back translation was reviewed/approved by the WHO. The GSED app was programmed in Amharic and piloted for 40 children aged 6–36 months, followed by its implementation by trained study nurses in a child development study in Bahir Dar. Results: Minor adaptations were made to terminologies and certain items were rephrased in the short and long forms. Modifications were made to physical objects used in the long form to make the items culturally appropriate and familiar. Local examples were used where necessary. The tool was administered to 364 children aged 6–36 months with an average administration time of 50–60 min. Quality control assessments by master trainers showed high agreement with assessments by trained study nurses throughout the study (average agreement: 91%). This study demonstrated the high acceptability and feasibility of the GSED tools. Conclusions: Local adaptations were required to contextualize the GSED tool for the Ethiopian setting. The preliminary experience with the GSED tool in Ethiopia is positive, with high-competency trained staff and ease of administration.